Periosteal Electrical Dry Needling as an Adjunct to Exercise and Manual Therapy for Knee Osteoarthritis: A Multicenter Randomized Clinical Trial. Issue 12 (December 2018) - Dunning, James; Butts, Raymond; Young, Ian; Mourad, Firas; Galante, Victoria; Bliton, Paul; Tanner, Michelle; Fernández-de-las-Peñas, César
Abstract : Objectives: To compare the effects of adding electrical dry needling into a manual therapy (MT) and exercise program on pain, stiffness, function, and disability in individuals with painful knee osteoarthritis (OA). Materials and Methods: In total, 242 participants (n=242) with painful knee OA were randomized to receive 6 weeks of electrical dry needling, MT, and exercise (n=121) or MT and exercise (n=121). The primary outcome was related-disability as assessed by the Western Ontario and McMaster Universities (WOMAC) Osteoarthritis Index at 3 months. Results: Individuals receiving the combination of electrical dry needling, MT, and exercise experienced significantly greater improvements in related-disability (WOMAC: F =35.504; P <0.001) than those receiving MT and exercise alone at 6 weeks and 3 months. Patients receiving electrical dry needling were 1.7 times more likely to have completely stopped taking medication for their pain at 3 months than individuals receiving MT and exercise (OR, 1.6; 95% confidence interval, 1.24-2.01; P =0.001). On the basis of the cutoff score of ≥5 on the global rating of change, significantly (χ 2 =14.887; P <0.001) more patients (n=91, 75%) within the dry needling group achieved a successful outcome compared with the MT and exercise group (n=22, 18%) at 3 months. Effect sizes were large (standardized mean differences >0.82) for all outcome measures in favor of the electrical dry needling group at 3 months. Discussion: The inclusion of electrical dry needling into a MT and exercise program was more effective for improving pain, function, and related-disability than the application of MT and exercise alone in individuals with painful knee OA. Level of Evidence: Level 1b—therapy. Prospectively registered February 10, 2015 onwww.clinicaltrials.gov (NCT02373631).